2020
DOI: 10.3390/ijms21103523
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal Intestinal Events in Alzheimer’s Disease (AD): Colonic Dysmotility and Inflammation Are Associated with Enteric AD-Related Protein Deposition

Abstract: Increasing evidence suggests that intestinal dysfunctions may represent early events in Alzheimer’s disease and contribute to brain pathology. This study examined the relationship between onset of cognitive impairment and colonic dysfunctions in a spontaneous AD model before the full development of brain pathology. SAMP8 mice underwent Morris water maze and assessment of faecal output at four, six and eight months of age. In vitro colonic motility was examined. Faecal and colonic Aβ, tau proteins, α-synuclein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 67 publications
6
41
0
Order By: Relevance
“…Additionally, pro-inflammatory cytokines IL-6 or IL-1β, as well as lipocalin-2 or TNF-α expression levels are increased in the colon of APP/PS1 mice by 3 and 6 months of age [ 125 ]. Similar results have been observed in SAMP8 mice, a spontaneous AD model, with colonic inflammation and high IL-1β levels [ 126 ]. Moreover, IL-1β was increased, while IFN-γ, IL-2 and IL-5 levels decreased in the brain from aged APP/PS1 mice [ 124 ].…”
Section: Diet Inflammation and Gut Microbiota In Ad Modelssupporting
confidence: 86%
“…Additionally, pro-inflammatory cytokines IL-6 or IL-1β, as well as lipocalin-2 or TNF-α expression levels are increased in the colon of APP/PS1 mice by 3 and 6 months of age [ 125 ]. Similar results have been observed in SAMP8 mice, a spontaneous AD model, with colonic inflammation and high IL-1β levels [ 126 ]. Moreover, IL-1β was increased, while IFN-γ, IL-2 and IL-5 levels decreased in the brain from aged APP/PS1 mice [ 124 ].…”
Section: Diet Inflammation and Gut Microbiota In Ad Modelssupporting
confidence: 86%
“…AD is one of the most common neurodegenerative disorders, characterised by a progressive memory decline, cognitive impairment, amyloid β1-42 (Aβ) plaque accumulation, neurofibrillary tangle of hyperphosphorylated tau (p-tau) protein and occurrence of neurogenic/inflammatory responses in the central nervous system ( Scheltens et al, 2016 ). In addition, AD patients are often characterized by functional digestive disturbances, including infrequent bowel movements, constipation, and defecatory disorder ( D’Antongiovanni et al, 2020b ; Pellegrini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, it has been proposed that alterations of enteric bacteria-neuro-immune network may contribute to the onset of bowel motor disturbances associated with AD ( Pellegrini et al, 2018a ; Mancuso and Santangelo, 2018 ). In this regard, pre-clinical and human studies have reported that AD is associated with changes in gut microbiota composition, colonic accumulation of Aβ and p-tau tangle-like structures as well as signs of enteric inflammation, which could lead to enteric motor dysfunctions ( Joachim et al, 1989 ; Puig et al, 2015 ; Piccarducci et al, 2019 ; Pellegrini et al, 2020 ). In this respect, interesting evidence obtained from studies on the Senescence-Accelerated Mouse-prone 8 (SAMP8) mouse model indicate that, in the early stages of AD, changes in gut microbiota composition and impairment of intestinal epithelial barrier (IEB) permeability can promote enteric AD protein accumulation, which, in turn, can shape enteric neurogenic/inflammatory responses, thus contributing to gut dysfunctions ( Pellegrini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is inconclusive whether AD pathology begins in the intestines. Some samples from AD patients show increased Aβ deposits in the intestines (152), and several AD mouse models corroborate increased Aβ plaques and hyperphosphorylated tau overexpression in the intestines and enteric nervous system as well as impaired gut motility and function and increased inflammation (152)(153)(154)(155). However, one study found no difference in gut motility and absorption between AD and control mice, though they detected intestinal Aβ and tau deposits in AD mice and AD patient samples (156).…”
Section: Neurological Diseasesmentioning
confidence: 99%